Development and optimization of high‐performance PEEK/CF/Nanosilica hybrid composites. (4th May 2021) - Lin, Leyu; Schlarb, Alois K.
Abstract : In the present study, tribological properties of PEEK/CF/nanosilica composites with distinct amounts of silica nanoparticles against steel were studied by using a block‐on‐ring tribometer followed by the characterizations of associated transfer films and polymer worn surfaces. The results demonstrate that the content of silica nanoparticles exerts an obvious influence on the friction and wear properties of PEEK/CF/nanosilica composites. Under low‐load conditions, the friction coefficient and specific wear rate exhibit opposite dependence on the nanosilica content. The friction coefficient decreases with increasing nanofiller content, while the specific wear rate increases with enhancing nanosilica loading. When the load conditions were changed toward high values, the divergence of the tribological properties becomes insignificant, which show less dependence on the nanosilica loading. Taking into account the practical applications of such composites, the composite containing 2 wt.% silica nanoparticles can serve as an excellent candidate for manufacturing tribological components in the practical applications.